Területi és ágazati érdekek a szocialista közlekedéshálózat alakulásában - Erdősi, Ferenc (Tér és Társadalom, 1987)
'Quasi-sociological' methods can reveal regional and sectoral pressures also in the socialist period of transport network development: most of the few post-war railway constructions served sectoral, particularly heavy industrial, interests. Frequent railway line liquidations following 1968 were again motivated by pressures from individual firms, wrapped up in the guise of national interests. But the negative consequences soon unveiled the fact that these liquidations were very harmful to regional, and finally to overall, interests. Most railway liquidations were contrary to codified regional development policies since they happened in backward regions which received state subsidies from earmarked spatial development funds. The M7 national highway leading to lake Balaton was traced according to the interests of the capital. But a section of the western M1 highway crossing the Kisalföld provides an example for the victory of regional concern for nature conservation. On the other hand, provincial interests often resulted in situations in which newly built access roads leading to villages located along county borders actually teared them away from their natural gravity zone. The development of long-distance bus line services bears the mark of the business interests of the state road transportation firms VOLÁN which are organized by counties. VOLÁN did not at all considered the interests of these who live in small villages, in the midst of accumulated disadvantages anyway, and who, in many instances, cannot reach either the nearest town or the county seat direct.